Disseminated Mycobacterium Tuberculosis and IgA Nephropathy. (1st November 2022) - Audley, Gordon; Davidson, Bianca; Jones, Erika; Price, Brendon; Rayner, Brian; Wearne, Nicola; Barday, Zibya
Abstract : Mycobacterium tuberculosis (MTB) is an under-recognised cause of genitourinary disease. IgA nephropathy (IgAN), a leading cause of glomerulonephritis worldwide, has been described as a rare consequence of disseminated MTB infection. In this case report, we present the first case of MTB associated IgAN in Africa. Finding IgAN on kidney biopsy in an MTB endemic area should prompt a thorough investigation for MTB to increase the chance of remission of IgAN and prevent inappropriate use of immunosuppression.